Pelaksanaan Legalisasi Tanah Wakaf - Azmi, Shofwan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Waqf land is a type of waqf of immovable objects intended for worship and muamalah facilities with the aim of prospering the people. Land that has been waqf has changed its original ownership from private property to belong to the community, the waqf land should be given legal protection to avoid misuse of ownership. Law No. 41 of 2004 concerning waqf and PP No. 28 of 1977 concerning the procedures for waqf property is a guideline for legalizing waqf land. The registration of the Waqf Pledge Deed (AIW) and the waqf certificate are authentic evidence of valid waqf land, without both waqf land being vulnerable to the law, because waqf land that has not been legalized can end up in a dispute between the parties concerned. The main factor that many waqf lands have not legalized is the lack of public knowledge of the laws that govern it. In the implementation of the legalization of waqf land, there are problems with the long processing time, a lot of costs, the lack of administrative requirements and the negligence of the staff of the National Land Agency office (BPN). In Islamic law, the legalization of waqf land is not explicitly explained, but there is a legal value in the Qur'anic verse: